Study of fundamental laser material interaction parameters in solid and powder melting - Ayoola, Wasiu Ajibola (Cranfield University, 2016)
This study attempts to develop a set of parameters controlling the bead profile of deposits in powder melting, based on the spatial energy distribution of laser. Four parameters, identified as the laser material interaction parameters were used to study the bead profile formation in powder melting. The focus is put on control of the dimensional accuracy of powder deposits independently of the optical set-up and laser system. In the initial stage to understand the effect of welding parameters on the development of the fusion zone, a solid metal with homogenous and known thermal properties was used. The results indicate that for large beam diameters, typically used in cladding, power density and interaction time control the depth of penetration and beam diameter and interaction time controls the weld width. However, for small beam diameters, typically used in powder bed additive manufacturing, it was found that it is more difficult to achieve steady state conduction welds due to high conduction losses to the bulk material and rapid transition to keyhole regime. Therefore, with small beam diameters it is challenging to achieve pure conduction welds, which should guarantee good quality of deposits and low spatter. In the second part, the melting behaviour of solid material and powder for the same material type was compared. The build height in powder melting depends on layer thickness of the deposited powder and energy density, which needs to be provided to fuse the powder to the workpiece, which is equivalent to penetration in laser welding of solids. Similar to solid melting, the build width in powder melting is controlled by beam diameter and the interaction time. It was also found that with small beam diameters and large particle sizes it is more difficult to generate keyhole in the base plate, as compared to solid material. Therefore, despite the presence of spatter in the process, a full keyhole is often not generated. A set of parameters to describe the conduction welding process based on spatial distribution of laser energy has been developed. This enables achievement of a particular weld profile with various optical set-ups and potentially transfers of results between machines. However, more complex melting characteristics of powder requires some additional factors to be included to develop a similar model for powders.